Pengaruh Edukasi Diet Dash (Dietary Approaches To Stop Hypertension) Terhadap Kepatuhan Diet dan Tekanan Darah Pada Penderita Hipertensi Dirumah Sakit Efarina Etaham Brastagi Tahun 2025 - Renta Manurung; Jeni Raulina Br Siregar (Jurnal Minfo Polgan, 2025)
Hypertension is a chronic disease whose prevalence continues to increase and is a major cause of serious complications such as stroke and heart disease. One effective non-pharmacological approach to controlling blood pressure is DASH (Dietary Approaches to Stop Hypertension) diet education. This study aims to analyze the effect of DASH diet education on diet compliance and blood pressure in hypertensive patients. This study used a pre-experimental one-group pretest-posttest design with a sample of 49 respondents selected through purposive sampling. DASH diet education was provided to respondents, followed by repeated measurements of diet compliance and systolic and diastolic blood pressure. Data were analyzed using the Wilcoxon Signed-Rank test and paired t-test. The results showed that DASH Diet Education significantly increased dietary compliance after education (p = 0.001). 0.000), and Diet Education significantly reduced systolic blood pressure (mean from 151.86 mmHg to 133.78 mmHg; p = 0.000), while Diet Education significantly reduced diastolic blood pressure (mean from 96.94 mmHg to 84.69 mmHg; p = 0.000). DASH diet education has been shown to be effective in improving dietary adherence and reducing systolic and diastolic blood pressure in patients with hypertension. This intervention can be used as a useful non-pharmacological approach for the ongoing management of hypertension in healthcare facilities.